Exploring physicochemical and cytogenomic diversity of African cowpea and common bean - Catarino, Sílvia (2021)
In sub-Saharan Africa, grain legumes (pulses) are essential food sources and play an important role in sustainable agriculture. Among the major pulse crops, the native cowpea (Vigna unguiculata) and introduced common bean (Phaseolus vulgaris) stand out. This paper has two main goals. First, we provide a comprehensive view of the available genetic resources of these genera in Africa, including data on germplasm collections and mapping biodiversity-rich areas. Second, we investigate patterns of physicochemical and cytogenomic variation across Africa to explore the geographical structuring of variation between native and introduced beans. Our results revealed that 73 Vigna and 5 Phaseolus species occur in tropical regions of Africa, with 8 countries accounting for more than 20 native species. Conversely, germplasm collections are poorly represented when compared to the worldwide collections. Regarding the nuclear DNA content, on average, V. unguiculata presents significantly higher values than P. vulgaris. Also, V. unguiculata is enriched in B, Mg, S, and Zn, while P. vulgaris has more Fe, Ca, and Cu. Overall, our study suggests that the physicochemical and cytogenomic diversity of native Vigna species is higher than previously thought, representing valuable food resources to reduce food insecurity and hunger, particularly of people living in African developing countries